2019
DOI: 10.1186/s40536-019-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender, affect, and math: a cross-national meta-analysis of Trends in International Mathematics and Science Study 2015 outcomes

Abstract: Understanding why women are consistently underrepresented in STEM fields has been a constant puzzle, with a consistent feature of the puzzle being performance in math. This study uses data from TIMSS exams to investigate cross-national gender differences in math-related affect, more precisely liking mathematics, confidence in mathematics, and valuing mathematics. We compared fourth and eighth graders to track any differences in these gender-related affective characteristics. Our findings suggest that despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
0
28
1
1
Order By: Relevance
“…Nonetheless, it is preferable that students are interested in their schoolwork, both because they are likely to experience more satisfaction in school and because they are likely to achieve better (e.g., Artelt et al, 2003). Given these benefits of having high levels of interest, it is problematic that a large body of research has found that girls tend to have less interest in mathematics than boys do (Hyde et al, 1990;Lippa, 1998;Preckel et al, 2008;Su et al, 2009;Frenzel et al, 2010). However, this gender gap in mathematics interest does not seem to be universal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is preferable that students are interested in their schoolwork, both because they are likely to experience more satisfaction in school and because they are likely to achieve better (e.g., Artelt et al, 2003). Given these benefits of having high levels of interest, it is problematic that a large body of research has found that girls tend to have less interest in mathematics than boys do (Hyde et al, 1990;Lippa, 1998;Preckel et al, 2008;Su et al, 2009;Frenzel et al, 2010). However, this gender gap in mathematics interest does not seem to be universal.…”
Section: Introductionmentioning
confidence: 99%
“…However, this gender gap in mathematics interest does not seem to be universal. Recent research using cross-national data from the Trends in Mathematics and Science Survey (TIMSS) has uncovered that in many countries the gender gap in mathematics attitudes, including interest in schoolwork, is reversed (Ghasemi and Burley, 2019;Reilly et al, 2019). These findings suggest that the correct question to ask is not why girls are less interested in math than boys are, because often the opposite holds.…”
Section: Introductionmentioning
confidence: 99%
“…Pipeline Programs for Women in STEM Despite a heavy investment in gender equality programs, there has been a subpar return with low overall attrition rates of women in STEM throughout their careers [46]. Notwithstanding ongoing efforts, women account for less than 13 % of engineers, 25 % of the STEM workforce, and 23 % of STEM professors [47][48][49][50].…”
Section: The Challenges Faced By Women In Stem Fieldsmentioning
confidence: 99%
“…Perempuan terlihat lebih mesra, lemah lembut, sensitif, emosional, bergantung dan penurut (Santrock, 2009). Beberapa hasil penelitian menunjukkan kesamaan proses perkembangan berfikir matematika dan prestasi matematika antara siswa laki-laki dan perempuan (Ajai, & Imoko, 2015;Nugraha & Pujiastuti, 2019;Lestari, Suesthi, & Wiyono, 2019;Ghasemi, & Burley, 2019;Kersey, Csumitta, & Cantlon, 2019;Kamid, Rusdi, Fitaloka, Basuki, & Anwar, 2020). Di pihak lain, ada peneliti yang melaporkan bahwa ada perbedaan dalam proses berpikir dan prestasi matematika, di mana siswa laki-laki umumnya lebih unggul dari siswa perempuan (Tommaso, Mendolia, & Contini, 2016;Kwanza, Maikudi, Taiwo, © Vintseh, Usman, Attah, & Alaku, 2018;Pambudi, Budayasa, & Lukito, 2018), khususnya pada keahlian visual matematis (Aini, & Hasanah, 2019).…”
Section: Pendahuluanunclassified